Current state and problems of agriculture in Ukraine - Fedulova, Irina; Kunytsia, Lyudmila (My University, 2011)
The main goal of the paper is to provide the general vision of the current state and problems of agriculture sector of Ukraine. The main tendencies observed in the sector were analysed with respect to their historical development. It was defined that the despite of the high potential of the agriculture in Ukraine, it remains underdeveloped and underinvested economic sector that causes negative tendencies in social and economic life of the rural areas. Also the detailed description of the crop and livestock production trends is provided in comparison to the previous stages of the sector development and with respect of farm producer’s ownership types. The paper particularly focuses on the ways of dealing with the current problems in order to stimulate the development of effective agriculture sector in Ukraine.
Keywords: сільсьгосподарський потенціал; тваринництво; рослинництво; растениеводство; сельскохозяйственный потенциал; животноводство; crop production; livestock production; agriculture potential; labour force; arable land; кафедра економіки праці та менеджменту; кафедра ділової іноземної мови та міжнародної комунікації